Two cases of long-lasting, sub-microscopic Plasmodium malariae infections in adults from coastal Tanzania - Tobias Schindler; Said Jongo; Fabian Studer; Maximilian Mpina; Grace Mwangoka; Sarah Mswata; Kamaka Ramadhani; Julian Sax; L. W. Preston Church; Thomas L. Richie; Marcel Tanner; Stephen L. Hoffman; et al. (Malaria Journal, 2019)
Abstract Background Malaria is endemic in Tanzania with majority of clinical cases caused by Plasmodium falciparum. Additionally, Plasmodium malariae and Plasmodium ovale spp. are also present and clinical manifestations caused by these infections are not well described. Clinical episodes caused by P. malariae infections are often characterized by a relatively mild illness with a low number of parasites, which can persist for long periods. In this report, two cases of P. malariae infections that were identified during a clinical trial evaluating the P. falciparum malaria vaccine candidate, PfSPZ Vaccine are described. The two participants were followed up and monitored for clinical and laboratory parameters to assess vaccine safety providing the opportunity to study clinical manifestations of P. malariae over 4 months. Case presentation Two young, healthy Tanzanian men infected with low density asexual blood stage P. malariae diagnosed by quantitative polymerase chain reaction (qPCR) are described. Retrospective analysis of collected and stored blood samples revealed that the two volunteers had constant asexual blood stage parasitaemia for more than 4 months. During the 132 days of infection, the volunteers’ vital signs, body temperature and serum biochemistry all remained within normal ranges. Haematological abnormalities, which were transiently outside normal ranges, were regarded as not clinically significant. During this time period, four consecutive evaluations of blood samples by thick blood smear microscopy conducted by an experienced microscopist were all negative, indicating the presence of low-density sub-microscopic infections. Conclusions The two cases of P. malariae infections presented here confirm the ability of this Plasmodium species to persist at low density in the human host for extended time periods without causing clinical symptoms. The presented data also demonstrate that clinical study sites in malaria endemic regions need to have a strong malaria diagnostic infrastructure, including the ability of capturing sub-microscopic parasitaemia and differentiation of Plasmodium species. Trial registration ClinicalTrials.gov: NCT02613520, https://clinicaltrials.gov/ct2/show/NCT02613520, Registered: November 24th 2015, Enrolment of the first participant to the trial: December 15th 2015, Trial was registered before the first participant was enrolled